A Look at Vocational Programming for the Secondary Educable Mentally Retarded - Georgia State Dept. of Education, Atlanta. Div. of Special Education; Georgia State Dept. of Education, Atlanta. Div. of Special Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
Presented is a curriculum guide for educable mentally retarded secondary school students in Georgia which features functional academics, physical development, social skills, and prevocational and vocational skills. Included are a work-study schedule for five levels (freshman through graduate), an explanation of school and work station sites, criteria for task performance, a list of work-in positions (such as building maintenance worker and teacher aide), and hints for establishing work-out positions. Specified are guidelines for the vocational program such as student need to understand that job placement is a privilege to be earned, and for teacher monitoring of students and job stations. Offered are grade-level scheduling plans including math, reading, social studies, and occupational exploration for grade 8, and work-out site experience coupled with siminars for seniors; alternate scheduling plans for students and off-period schedules for teachers (for purposes such as planning and home visitation). Listed are regular courses for mainstreaming. Discussed are aspects of salaries such as pay, provisions, trainee criteria, and child labor provisions. Also discussed are parent involvement, public relations, curriculum materials, and learning centers. Included are a termination agreement, budget contract, a list of state laws regulating employment of children, teacher made award sheets, and evaluation forms. (MC)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Curriculum Guides; Exceptional Child Education; Mental Retardation; Mild Mental Retardation; Prevocational Education; Scheduling; Secondary School Students; Social Development; Vocational Education; Work Study Programs; Georgia; Reports, Research